Clinical efficacy, radiographic and safety findings through 5 years of subcutaneous golimumab treatment in patients with active psoriatic arthritis: results from a long-term extension of a randomised, placebo-controlled trial (the GO-REVEAL study) - Kavanaugh, Arthur (BMJ Publishing Group, 2014)
OBJECTIVES: Assess golimumab's long-term efficacy/safety in psoriatic arthritis (PsA). METHODS: Adults with active PsA (≥3 swollen and tender joints, active psoriasis) were randomly assigned to subcutaneous placebo, golimumab 50 mg, or golimumab 100 mg every 4 weeks (q4wks) through wk20. All patients received golimumab 50 mg or 100 mg q4wks from wk24 forward. Methotrexate was allowed and taken by approximately half the patients. Findings through 5 years are reported herein. Efficacy assessments included ≥20% improvement in American College of Rheumatology (ACR20) response, C-reactive-protein-based, 28-joint-count Disease Activity Score (DAS28-CRP) response, ≥75% improvement in Psoriasis Area and Severity Index (PASI75) scores, and PsA-modified Sharp/van der Heijde scores (SHSs). RESULTS: 126/405 (31%) randomised patients discontinued treatment through wk252. Golimumab was effective in maintaining clinical improvement through year-5 (ACR20: 62.8–69.9%, DAS28-CRP: 75.2-84.9% for randomised patients; PASI75: 60.8–72.2% among randomised patients with ≥3% body surface area involvement) and inhibiting radiographic progression (mean changes in PsA-modified SHS: 0.1–0.3) among patients with radiographic data. While concomitant methotrexate did not affect ACR20/PASI75, it appeared to reduce radiographic progression. No new safety signals were identified. Antibodies-to-golimumab occurred in 1.8%/10.0% of patients with/without methotrexate). CONCLUSIONS: Long-term golimumab safety/efficacy in PsA was demonstrated through 5 years. TRIAL REGISTRATION NUMBER: NCT00265096.